2018
DOI: 10.1007/s10295-018-2036-2
|View full text |Cite
|
Sign up to set email alerts
|

Corrections to: Enhanced lincomycin production by co‑overexpression of metK1 and metK2 in Streptomyces lincolnensis

Abstract: In the online published article, row value “pIB139-metK1-metK2” in table 1 has been processed incorrectly. The correct table is given below

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Escherichia coli strains were cultured at 37°C in Luria Bertani (LB) medium and supplemented with antibiotics as required (Sambrook and Russell 2012). S. lincolnensis strains were cultured at 30°C with shaking at 220 rpm in liquid TSBY medium for genomic DNA extraction (Xu et al 2018). S. lincolnensis strains were grown on MGM medium for spore production (Xu et al 2019).…”
Section: Strains Plasmids and Cultivation Conditionsmentioning
confidence: 99%
“…Escherichia coli strains were cultured at 37°C in Luria Bertani (LB) medium and supplemented with antibiotics as required (Sambrook and Russell 2012). S. lincolnensis strains were cultured at 30°C with shaking at 220 rpm in liquid TSBY medium for genomic DNA extraction (Xu et al 2018). S. lincolnensis strains were grown on MGM medium for spore production (Xu et al 2019).…”
Section: Strains Plasmids and Cultivation Conditionsmentioning
confidence: 99%
“…Intracellular SAM was extracted and detected as described (Xu et al 2018). In brie y, 200 mg frozen cells were transferred to 1.5 mL microcentrifuge cubes and extracted with 1 mL of 1 mol/L formic acid at 4 °C for 2 h. The samples were centrifuged at 10000 rpm for 10 min at 4 °C to collect the supernatant for determination.…”
Section: Determination Of Intracellular Sam Concentrationmentioning
confidence: 99%
“…Given the high clinical importance of lincomycin, enhancement of lincomycin A production or reduction of lincomycin B production in S. lincolnensis have been performed in many studies by strain screening (Ye et al 2009;Meng et al 2013;Huang et al 2017), fermentation engineering (Xue et al 2009; Lee et al 2014; Zhuang et al 2019) or genetic manipulation (Pang et al 2015;Xu et al 2018). All the above studies focused on optimization of medium composition and process conditions or screening strains with more productivity.…”
Section: Introductionmentioning
confidence: 99%
“…They promoted spiramycin production by increasing the concentration of ethylmalonyl-CoA via over-expressing the crotonyl coenzyme A reductase gene. S-Adenosylmethionine (SAM) is widely known to be a methyl donor to secondary metabolites [10,11]. Experimental results from Streptomyces lividans showed that overexpression of the metK gene that encodes SAM synthetase not only promotes higher methyl donor concentrations, but also stimulates the expression of a positive regulatory gene actII-ORF4 for the actinorhodin (Act) gene cluster, thereby leading to enhancement of Act biosynthesis in S. lividans [12,13].…”
Section: Introductionmentioning
confidence: 99%